An Analysis Of The Process Of Experiential Function In Writing Explanation Text at Tenth-Grade Students Of Smk Swasta Budisatrya Medan - Hartatis, Hartatis Ayu; Tampubolon, Sahlan; Manurung, Lastri Wahyuni (Lembaga Riset dan Inovasi Almatani, 2024)
The purpose of this research was to find out the types of experiential function processes found in the explanation text writing of class X students of SMK. Swasta Budisatrya Medan, and the most dominant process found in the explanation text of class X students of SMK Swasta Budisatrya Medan. The method used in analyzing the data of this research is the descriptive qualitative method. The data in this study were taken from 34 students' writings. The data used were 567 clauses containing six types of experiential function processes. From the data obtained, the material process occurs 246 times (65.2%), the mental process occurs 32 times (8.5), the relational process occurs 80 times (21.2%), the behavioral process occurs two times (0.5%), the verbal process occurs 13 times (3.5), the existential process occurs four times (1.1%). This study shows that the material process is the most used experiential function process in students' explanation text writing. In writing a text, students use the experiential function process to show the meaning they want to convey. In writing explanation texts, students use more process material because the experiential function process is related to explanation texts, namely in writing explanation texts using action verbs in action work in their descriptions according to the social function of explanation texts.